STRUKTUR KOMUNITAS EKOSISEM PADANG LAMUN PADA DAERAH INTERTIDAL DI PANTAI SANUR, BALI - Made Ayu Pratiwi; Ni Made ERNAWATI (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2018)
Coastal ecosystem is a productive ecosystem and has high ecological and economic value. Coastal ecosystem components, consist of coral reefs, seagrass beds, mangroves and various types of biota. The seagrass ecosystem is one of the most unique coastal ecosystems because the seagrass can live well in high salinity conditions. Seagrass ecosystem in Bali Island has many adventages and widely used for marine tourism activities. One of the marine tourism sites, that take advantage of the beauty of the seagrass ecosystem in Bali is Sanur beach. The utilization of seagrass ecosystem for marine tourism activities might be influence the structure of seagrass community. Therefore, the study about Community Structure of Seagrass Ecosystem at Intertidal Area in Sanur Beach is very important to carried out in order to investigate the structure of the seagrass ecosystem community. Samples were taken in the intertidal zone at six observation stations. At each station, it was conducted three times perpendicular repetition to the shoreline. Seagrass observation was done by using quadratic transect (50 × 50 cm). The types of seagrass found in Sanur Beach were 6 species, namely Cymodocea serrulata, Cymodocea rotundata, Halophila ovalis, Halodule uninervis, Halodule pinifolia, and Syringodium isoetifolium. Cymodocea serrulata is a seagrass-type found in every observation station, and it able to live well in Sanur Beach water characteristics. The highest average of seagrass species density is shown by the Cymodocea serrulata species of 175.11 stands/m2, while, the highest average of seagrass species density is shown by the Halodule pinifolia species of 27.33 stands/m2. The average of diversity, uniformity and dominance index at Sanur Beach reach 0.8682; 0.7347; and 0.4987, respectively. In Sanur Beach area, the seagrass has high uniformity value and stable community. The instability community has been found at station 2 when the dominance of Cymodocea serrulata species was occurred. Keywords: Community structure; Sanur Beach; seagrasse cosystem